1972
DOI: 10.1002/1097-0142(197203)29:3<784::aid-cncr2820290336>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal rhabdomyosarcoma of the middle ear

Abstract: Embryonal rhabdomyosarcoma of the middle ear, as previously reported in the literature, is an almost uniformly lethal entity. An unusual case presenting with bone destruction and later demonstrating a metastatic locus has achieved a relatively long‐term NED survival status. Adequate radiotherapy, when combined with both concomitant and then maintenance chemotherapy, may not only control the local tumor but delay, prevent, or treat peripheral macroscopic or microscopic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

1972
1972
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…McNeer et al (1968), in an extensive review of 653 cases of soft tissue sarcomas of all types, showed that radiotherapy may markedly improve survival periods of patients with such tumouis. Edland (1965) and Nelson (1968) regarded embryonal rhabdomyosarcoma as a tumour of moderate radiosensitivity. Conte and Sagerman (1971) recommended aggressive irradition once the tumour is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…McNeer et al (1968), in an extensive review of 653 cases of soft tissue sarcomas of all types, showed that radiotherapy may markedly improve survival periods of patients with such tumouis. Edland (1965) and Nelson (1968) regarded embryonal rhabdomyosarcoma as a tumour of moderate radiosensitivity. Conte and Sagerman (1971) recommended aggressive irradition once the tumour is diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…However, useful dose-time fraction data is scarce. Low dose control (less than 6,000 rads) of minimal disease has been documented by many authors (8,10,13,15,20,21,25,27,30). Table I11 demonstrates that for all soft tissue sarcomas, the better cure rates are for microscopic disease and doses above 6-7,000 rads (10, 12, 15-17, 23,25,29-31,34).…”
Section: Diversity Of Treatmentmentioning
confidence: 92%
“…planes and muscular compartments often recur with local excision alone. Tumors arising in the buttocks and shoulder girdle often recur even with hemipelvectomy or shoulder disarticulation (16,25). sarcomas often eventually require amputation (1,11,13,18,23).…”
Section: Diversity Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1965'de Edland ilk kez tam cerrahi rezeksiyon yapılamayan bir olguda yüksek doz RT kullanmıştır (4) . Sonrasında adjuvan kemoterapinin (KT) tedaviye eklenmesi ile RMS'da çok-lu tedavi yaklaşımı oluşturulmuş ve RMS ile ilgili geniş verilere ulaşılmıştır.…”
Section: Rabdomyosarkomunclassified